La Loire moyenne naviguée au XIXe siècle : représentations, réglementation et aménagement - Yves Lecoeur (VertigO)
The middle Loire, in the heart of France, constitutes an important axis of transport but the conditions of navigation are difficult. In summer, the irregular water flow transforms the Loire into a river of sand. Navigation techniques, river maintenance and engineering, and the regulations for sharing the space between different economic activities are not able to prevent the decline of waterway transport after 1850. This decline was caused by roads improvement of and extension of the railroad network. The reflexion on the waterway and its future is accompanied by numerous debates and conflicts.